PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA KANTOR SEKRETARIAT DPRD KABUPATEN SIDENRENG RAPPANG - Anastasia D'Ornay; Maskur Hasan (Jurnal Ilmu Manajemen Profitability, 2019)
The objectives of this study are (1) to find out whether work discipline and work environment have a partial effect on the performance of the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency. (2) To find out whether work discipline and work environment have a simultaneous effect on the performance of the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency. Data collection techniques in this study are the method of observation, interviews, and literature study. In this study, the population is the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency, totaling 35 people. For this study to provide generalizations with a very small error rate, and considering the population is only 35 people, this research uses a sampling technique, namely saturated sampling (census). Thus the number of samples in this study was 35 people. The results showed that (1) work discipline partially affected the performance of the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency. where the results obtained by work discipline have a value of 4.062 t table. 2.024 and the significance level of t is less than 0.05 (sig = 0.000 0.05). (2). The work environment has a partial effect on the performance of the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency. Where the results obtained in the work environment have an account value of 3.182 t-table 2.024 and the significance level of t is less than 0.05 (sig = 0.003 0.05). (3). Work discipline and work environment simultaneously (simultaneously) affect the performance of the state civil apparatus at the secretariat office of the DPRD Sidendeng Rappang Regency. It can be seen that work discipline and work environment provide a calculated F value of 123.048 which is greater than the F table which is 5.18 with a probability value of 0.000 which means it is below the significance value of 0.05.